The Red violin - Fichman, Niv; Girard, Francois; McKellar, Don (Telefilm Canada, 1998)
Traces the creation and history of a blood-red violin and chronicles the stories of people who owned it over a period of three hundred years, starting from 17th century Italy up to the present day in Montreal, where it is to be auctioned off.